Investigation of Microbial Contamination in the Clinic and Laboratory of the Prosthodontics Department of Dental School - Sharzad Taheri; Ghazaleh Shahabinezhad; Molook Torabi; Soodabeh Torabi Parizi (Association of Support to Oral Health Research (APESB), 2021)
Objective: To determine the level of clinical contamination in the clinic and laboratory of the prosthodontics department of Kerman Dental School. Material and Methods: Clinical surfaces of the dental units, the laboratory, and the professors' lounge of the prosthodontics department were randomly sampled. The sampled surfaces included the dental units' console, light switch, light handle, headrest, and air-water spray syringe in the clinic, plastering tables, buttons of the vibrator, polishing, and trimmer machines, acryl tables, handles of pressure pot and press machine, handpiece holders, work desks, and drawer handles in the laboratory, and desks, computer mouse and keyboard, telephone sets, and doorknob in the professor's lounge. The samples were examined for the type and growth of microorganisms. The data were entered into SPSS, where they were analyzed using the chi-square test at the 0.05 significance level. Results: Of all the samples taken, 89.9% showed microbial contamination. The most common type of contamination was fungus (34.8%) and the least common types were Enterococcus faecalis and Staphylococcus epidermidis (1.1%). The second and third most common types of bacteria in the samples were Staphylococcus aureus (18%) and Pseudomonas aeruginosa (12.4%), respectively. There was no significant difference between the frequencies of microbial contamination in the clinic, the laboratory, and the professors' lounge. Conclusion: Given the strong chance of cross-infection in the examined department and laboratory, it is necessary to enforce protocols for proper disinfection of surfaces before, between and after treatments.